PENERAPAN TERAPI AKTIVITAS KELOMPOK BERMAIN KUARTET (KARTU) PADA PASIEN ISOLASI SOSIAL MENARIK DIRI - Riko Sandra Putra Riko; Diana H.Soebyakto (Jurnal Kesehatan dan Pembangunan, 2023)
Social isolation is an attempt to avoid interactions and relationships with other people. Patients who experience social isolation are characterized by flat affect, sad effects, wanting to be alone, inability to meet other people's expectations, and withdrawal. The purpose of this study was to find out the description of the application of Quartet Play Group Activity Therapy (cards) in social isolation patients withdrawing. The type of research used in this research is qualitative descriptive, namely in the form of research with a case study method or approach. The research results obtained based on the observation sheet assessed from the two clients showed that there was a difference where client I Mr. "A" experienced an increase where the client was able to get acquainted and interact with other people even though the client was still unable to provide feedback or provide an assessment to other people, while client II Mr "S" experienced an increase where the client was able to get to know and interact with other people even though the client still looked nervous and could not provide feedback or assessments to other people. For group activity therapy, the quartet game is successful because the client has practiced and been trained how to improve his socialization skills. The conclusion of this study is that there is an increase in interaction with social isolation clients with the application of TAK playing quartet. This can be an agenda for clients of social isolation so that there is an increase in health